Association of Preoperative Neutrophil to Lymphocyte Ratio with Early Postoperative Acute Kidney Injury Following Isolated Off-Pump Coronary Artery Bypass Grafting (Bangladesh Heart Journal, 2024)
Objective: Acute kidney injury (AKI) is a frequent complication after off-pump coronary artery bypass grafting (OPCAB) that complicates recovery, increases treatment cost and mortality. Neutrophil to lymphocyte ratio (NLR) is a systemic inflammatory marker easily derived from complete blood count that has many prognostic potentials. The purpose of this study was to evaluate if there is an association of preoperative NLR with early postoperative AKI following isolated OPCAB. Methods: This cross-sectional study was carried out in the Department of Cardiac Surgery, National Institute of Cardiovascular Diseases (NICVD) on a total of 60 patients aged 31-70 years with no preoperative renal dysfunction undergoing isolated OPCAB between August 2021 and July 2022. Group A included 30 patients with preoperative NLR < 2.65 and Group B included 30 patients with preoperative NLR ≥ ≥≥2.65. Patients were monitored for development of early postoperative AKI according to serum creatinine criteria of Kidney Disease Improving Global Outcomes (KDIGO) 2012 guideline. Results: Two patients from group A and twenty patients from group B developed early postoperative AKI (p < 0.001). Events of AKI were significantly higher in group B patients at all postoperative time points. Multivariate binary logistic regression analysis revealed preoperative NLR ≥ ≥≥2.65 as an independent predictor of early post OPCAB AKI (p = 0.004, OR = 13.746). In receiver operating curve (ROC) analysis area under curve (AUC) was 0.933 (95% CI 0.874-0.992, p < 0.001). It showed 90.91% sensitivity and 73.7% specificity at the pre-set cut off value of NLR at 2.65 where optimal predictability of post-OPCAB AKI occurred with 66.67% positive predictive value, 93.33% negative predictive value and 80% accuracy. Conclusion: Preoperative NLR is significantly associated with early postoperative AKI following isolated OPCAB and therefore it should be incorporated in routine clinical practice for early prediction of AKI and implementing timely preventive strategies.(Bangladesh Heart Journal 2024; 39(2): 151-160